Perception of Spanish University Students of the Bachelor’s Degree in Teaching about the mention in Music Education - Pérez-Eizaguirre, Miren; Morales, Ángela; Cuenca-Rodríguez, Mª Elena; Privado, Jesús (Revista Complutense de Educación, 2024)
The knowledge that currents students have about the mentions of the teaching degrees is a field of interest in order to find out where they stand with regard to their choices in relation to their professional opportunities. This research aims to explore the differences in the perception of the mentions according to gender, the degree studied (double degree or Infant/Primary) and the year (2nd, 3rd, 4th or 5th year) and whether the fact of having previous musical studies influences the perception of the mentions. We also analysed the role played in this perception by the fact of having worked on musical aspects at school. A questionnaire was administered to 337 students in years 2, 3, 4 and 5 of the Bachelor’s Degree in Early Childhood Education, Master’s Degree in Primary Education and Double Degree in Early Childhood Education and Master’s Degree in Primary Education at the Autonomous University of Madrid, the University of Castilla-La Mancha, the University of Salamanca and the University of Murcia. The data were first analysed by carrying out preliminary statistical analyses of the main measures of the questionnaire. Secondly, an Exploratory Factor Analysis was carried out and finally, differences were studied using Student’s t-tests. Finally, associations between the measures of perception of mentions and the rest of the categorical measures were studied using Pearson’s χ2 tests, in addition to the calculation of Kramer’s V as an index of association. We conclude by insisting on the need for more information regarding the definition of the mentions and their professional opportunities for current students.